SPECIAL issue on the new public administration: global challenges-local solutions (1997)
The articles presented here review selected currents of thought, initiatives and experiences circulating during the meeting. They have been chosen for their intrinsic interest, as well as for their representativeness. For this reason, the selection includes semi-official reviews, drawn up by officials, of work in progress, together with more conventional scholarly articles. The former present an unusual and, in some respects, a limited or uncritical view of events, but are none the less revealing of perceptions and standpoints of officialdom that are rarely articulated outside departmental meeting rooms: they deserve careful consideration. The articles appear in the order in which they were presented at the conference, so as to reflect the conceptual framework and tempo of the meeting. This essay introduces the themes of the conference, namely, organization, people and services; it reviews issues of special interest to developing, small or island states, and suggests future avenues for scholarly inquiry in the field of public administration. - Reproduced
Keywords: Public administration